Virtual Reality Critical Thinking Training of Engineers in the Vertical Transportation Industry - Yavar Jarrah-Nezhad; Luis A. Paipa-Galeano; Cesar A. Bernal-Torres; Wilmer Garzon-Alfonso; Yamid Delghans-Jacome; Andres Felipe Paez-Caicedo (IEEE Access)
Concerns have emerged regarding the expenses associated with integrating virtual reality into the digital transformation of companies, stemming from costs related to 3D software development and procurement of headsets. Despite the acknowledged benefits of experiential learning in military training, education and medicine, industrial adoption of virtual reality remains constrained. This study delves into the distinctive advantages of virtual reality in the elevator industry and proposes a cost-effective and innovative virtual reality (VR) training solution and evaluation model aimed at improving the learning outcomes of engineers in the field, grounded in the critical thinking theory. The proposed model seeks to capitalize on the benefits of VR in projects geared towards digital transformation by identifying “meta-requirements” and “principal designs” through a design science research method focused on problem solving. This approach has potential applications in other domains. Our methodology employs a unique strategy to develop a virtual reality experiential training program that harnesses engineers’ cognitive potential to enhance their critical thinking skills. To evaluate the effectiveness of this approach, we conducted a comparative analysis with a control group trained through traditional digital methods, concentrating on “decision-making and problem-solving” as well as “thinking through hypothesis testing.” Engineers undergoing virtual reality training exhibited heightened motivation, emotional engagement, and curiosity levels toward the subject, providing detailed accounts of their experiential training in relation to physical space and time. The “learning by doing” approach resulted in a 15% enhancement in critical thinking among participants, along with a notable 44% improvement in recognition memory.